2011
DOI: 10.1038/nature10188
|View full text |Cite
|
Sign up to set email alerts
|

De novo cardiomyocytes from within the activated adult heart after injury

Abstract: A significant bottleneck in cardiovascular regenerative medicine is the identification of a viable source of stem/progenitor cells that could contribute new muscle after ischaemic heart disease and acute myocardial infarction1. A therapeutic ideal—relative to cell transplantation—would be to stimulate a resident source, thus avoiding the caveats of limited graft survival, restricted homing to the site of injury and host immune rejection. Here we demonstrate in mice that the adult heart contains a resident stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
642
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 599 publications
(669 citation statements)
references
References 24 publications
21
642
2
4
Order By: Relevance
“…These inadequacies may be overcome by 2PLSM. As such, a new line of studies has started to develop 2PLSM protocols to investigate electrical activity [25] or Ca 2+ signaling [17,26,27] in intact heart preparations, but to our knowledge, our study is the first to measure V m and intracellular Ca 2+ in the same preparation by 2PLSM near-simultaneously. Thus, we describe novel protocols that enable ratiometric 2P measurements of cellular V m and therefore electrical activation, as well as intracellular Ca 2+ cycling after simultaneous loading of the respective fluorescent dyes Di-4-ANEPPS and Fura-2/AM.…”
Section: Discussionmentioning
confidence: 99%
“…These inadequacies may be overcome by 2PLSM. As such, a new line of studies has started to develop 2PLSM protocols to investigate electrical activity [25] or Ca 2+ signaling [17,26,27] in intact heart preparations, but to our knowledge, our study is the first to measure V m and intracellular Ca 2+ in the same preparation by 2PLSM near-simultaneously. Thus, we describe novel protocols that enable ratiometric 2P measurements of cellular V m and therefore electrical activation, as well as intracellular Ca 2+ cycling after simultaneous loading of the respective fluorescent dyes Di-4-ANEPPS and Fura-2/AM.…”
Section: Discussionmentioning
confidence: 99%
“…It may be argued that the voltage signals measured at the scar border in WT1;VSFP2.3 +;+ mice could have originated from the minute number of individual myocytes expressing the protein rather than nonmyocytes. The spurious expression of VSFP2.3 in myocytes (∼0.06% in the border zone) may potentially be explained by WT1-expressing cell progeny among myocytes (31,32) or VSFP2.3 trafficking via the observed tunneling nanotubes [if they form continuous plasma membrane conduits as reported in some cell culture models (27)]. However, if VSFP2.3 signals in WT1; VSFP2.3 +;+ mice had originated from myocytes, then one would expect to also observe them in other ventricular tissue regions where the fraction of VSFP2.3 expressing myocytes, if anything, is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Given to mice intravenously, SCA1 þ cells that were positive for CXCR4 migrated to the injured myocardium and differentiated into cardiomyocytes in a mouse MI model (Oh et al, 2003(Oh et al, , 2004. Further studies have shown that cells positive for SCA1 and Wilm's tumor 1 (Wt1) isolated from mouse heart are able to give rise to de novo cardiomyocytes that structurally and functionally integrate with resident muscle after myocardial injury (Smart et al, 2011). Chong et al (2011) have recently demonstrated that a population of SCA1 þ and platelet-derived growth factor receptor alpha (PDGFRa) positive cells derive from the proepicardium of mouse heart has capacity for clonogenic propagation, long-term in vitro growth, and multilineage differentiation both in vitro and in vivo.…”
Section: C-kit 1 Cscsmentioning
confidence: 99%
“…Recently, Gyongyosi et al (2010) have shown that HPC enhances migration and recruitment of hematopoietic stem cells (HSC) and mesenchymal stem cells (MSC) to infarcted myocardium in a porcine myocardial ischemiareperfusion model. Oh et al, 2003;Oh et al, 2004;Smart et al, 2011;Chong et al, 2011.…”
Section: Signaling Factors and Pathways Involved In Migration Of Cscsmentioning
confidence: 99%